Corrigendum: High-Protein Energy-Restriction: Effects on Body Composition, Contractile Properties, Mood, and Sleep in Active Young College Students - Roth, Christian; Rettenmaier, Lukas; Behringer, Michael (Frontiers in Sports and Active Living, 2021)
Background: It is often advised to ensure a high-protein intake during energy-restricted diets. However, it is unclear whether a high-protein intake is able to maintain muscle mass and contractility in the absence of resistance training. Materials and Methods: After 1 week of body mass maintenance (45 kcal/kg), 28 male college students not performing resistance training were randomized to either the energy-restricted (ER, 30 kcal/kg, n = 14) or the eucaloric control group (CG, 45 kcal/kg, n = 14) for 6 weeks. Both groups had their protein intake matched at 2.8 g/kg fat-free-mass and continued their habitual training throughout the study. Body composition was assessed weekly using multifrequency bioelectrical impedance analysis. Contractile properties of the m. rectus femoris were examined with Tensiomyography and MyotonPRO at weeks 1, 3, and 5 along with sleep (PSQI) and mood (POMS). Results: The ER group revealed greater reductions in body mass (1 −3.22 kg vs. 1 1.90 kg, p < 0.001, partial η² = 0.360), lean body mass (1 −1.49 kg vs. 1 0.68 kg, p < 0.001, partial η² = 0.152), body cellmass (1 −0.85 kg vs. 1 0.59 kg, p < 0.001, partial η² = 0.181), intracellular water (1 −0.58 l vs. 1 0.55 l, p < 0.001, partial η² = 0.445) and body fat percentage (1 −1.74% vs. 1 1.22%, p < 0.001, partial η² = 433) compared to the CG. Contractile properties, sleep onset, sleep duration as well as depression, fatigue and hostility did not change (p > 0.05). The PSQI score (1 −1.43 vs. 1 −0.64, p = 0.006, partial η² = 0.176) and vigor (1 −2.79 vs. 1 −4.71, p = 0.040, partial η² = 0.116) decreased significantly in the ER group and the CG, respectively. Discussion: The present data show that a high-protein intake alone was not able to prevent lean mass loss associated with a 6-week moderate energy restriction in college students. Notably, it is unknown whether protein intake at 2.8 g/kg fat-free-mass prevented larger decreases in lean body mass. Muscle contractility was not negatively altered by this form of energy restriction. [TRUNCATED]